Pengaruh Strategi Critical Incident terhadap Hasil Belajar Menulis Karangan Narasi Siswa Kelas V SDN 19 Malela Kecamatan Suli - Rahmatiah Rahmatiah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The aim of this study was to determine the effect of the critical incident strategy on learning outcomes in writing narrative essays. This research is a descriptive type. The population of this study were fifth grade students at SDN 19 Malela for the 2022/2023 academic year, consisting of one class. The sample in this study were all Class V students at SDN 19 Malela, Suli District, totaling 27 students. Sampling used a total sampling technique. Data collection techniques used in this study were tests (pre-test and post-test), observation and documentation. Learning outcomes after applying active learning strategies based on calculations with 26 degrees of freedom, produce t-count = 5.0144 and t-table = 2.056. The results of these calculations show that t count ≥ t table (5.0144 ≥ 2.056). It can be concluded that the use of active learning strategies in critical incidents has an impact on the learning outcomes of fifth grade students at SDN 19 Malela, Suli District, Luwu Regency.